The morphology of the burgh (Scottish Historical and Archaeological Internet Reports, 2009)
The current layout of the town can be described broadly as having two main axes, one running east-west (comprising the High Street and Westgate), and one running south from the harbour, which also includes Victoria Street and Quality Street. There are additional street that developed to the north and south of the High Street axis, and further development to the east of Quality Street. One of the most interesting questions about the growth and layout of North Berwick relates to which of these two streets emerged first. A study of the early maps of North Berwick goes some way to giving an understanding of how the town grew.